PENGEMBANGAN BUKU CERITA PENDEK DIGITAL BERBASIS ETNOMATEMATIKA UNTUK MENINGKATKAN PEMAHAMAN KONSEP PENJUMLAHAN DAN PENGURANGAN BILANGAN ASLI DI KELAS II SEKOLAH DASAR - Elisa Putri Yuniar Rizqi Maulidiah; I Ketut Suastika; Nyamik Rahayu Sesanti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to develop a digital short storybook based on ethnomathematics that is feasible, practical, and effective for improving the understanding of addition and subtraction of natural numbers in second-grade elementary school students. The type of research uses the ADDIE development research design, which includes the analysis stage, the design stage, the development stage, the implementation stage, and the evaluation stage. This research was conducted on fourth-grade students with a total of 28 participants. The research and development instruments used included material expert validation sheets, media expert validation sheets, and student response questionnaires. The results of the material expert validation test scored 89.15, categorized as